Pengaruh Brand Image, Brand Trust dan Company Reputation Terhadap Loyalitas Pelanggan - Doni Marlius; Febi Anwar (JURNAL PUNDI, 2023)
Competition in the world is currently a challenge for every company because of the many product brands in the electronics industry such as smartphones. The purpose of this study was to examine whether there is an effect of Brand Image, Brand Trust and Company Reputation on customer loyalty. This research was conducted by distributing questionnaires to the community in the city of Padang. Testing and data management using SPSS with the help of multiple regression and correlation methods. In testing this hypothesis using multiple linear regression testing, descriptive test, t-test and Cronbach Alpha consumer choice is used to measure the validity and reliability, testing that has been done that all variables show valid and reable. Based on the results of the partial test (t test), brand image has a significant effect on customer loyalty. where it is the brand image has a t-count value greater than the t-table with a sign value, thus the brand image statistically has an influence on customer loyalty, brand trust has a significant effect on customer loyalty. In which case, brand trust has a t-count value greater than t-table with a sign value, thus brand trust statistically has an effect on customer loyalty and company reputation has a significant effect on customer loyalty. In which case, company reputation has a t-value greater than the t-table with a sign value, thus company reputation statistically has an influence on customer loyalty.